Aspects of the economics of an ageing population: Submission to a call for evidence from House of Lords Economic Affairs Select Committee - Philip Booth (Institute of Economic Affairs (IEA), 2003)
This submission responds to the call for evidence. It is structured as follows. It begins with a brief answer to a number of the questions put by the Committee. In Appendices one to three, more detailed evidence is provided which, in each case, relates to one or more of the questions. Appendices two and three consist of previously published papers.
Keywords: 330; Population development; Ageing population; Social change; Great Britain; Bevölkerungsentwicklung; Alternde Bevölkerung; Sozialer Wandel; Großbritannien